2020
DOI: 10.1021/acsanm.9b02558
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nanoscopic Cu/Diamond Interfaces Prepared by Surface-Activated Bonding: Implications for Thermal Management

Abstract: The microstructures of Cu/diamond interfaces prepared by surface-activated bonding at room temperature are examined by cross-sectional scanning transmission electron microscopy (STEM). A crystalline defect layer composed of Cu and diamond with a thickness of approximately 4.5 nm is formed at the as-bonded interface, which is introduced by irradiation with an Ar beam during the bonding process. No crystalline defect layer is observed at the 700 °C-annealed interface, which is attributed to the recrystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…After annealing at 400 °C, the increased amorphous layer thickness is more helpful in the relaxation of the stress. The amorphous layer thickness increase is unlike the heterointerfaces fabricated by SAB, in which the amorphous layer thickness decreased with increasing annealing temperature due to the recrystallization of the amorphous layer [22][23][24][25][26]. The main difference is no oxygen atoms detected in the SAB-fabricated interface because the bonding processes were conducted in the extremely high-level vacuum condition.…”
Section: Resultsmentioning
confidence: 96%
“…After annealing at 400 °C, the increased amorphous layer thickness is more helpful in the relaxation of the stress. The amorphous layer thickness increase is unlike the heterointerfaces fabricated by SAB, in which the amorphous layer thickness decreased with increasing annealing temperature due to the recrystallization of the amorphous layer [22][23][24][25][26]. The main difference is no oxygen atoms detected in the SAB-fabricated interface because the bonding processes were conducted in the extremely high-level vacuum condition.…”
Section: Resultsmentioning
confidence: 96%
“…[ 51,52 ] Reports have shown that the TBR of an as‐bonded Cu/diamond interface with a 4.5 nm‐thick intermediate layer is in good agreement with the value calculated by the phonon diffuse mismatch model. [ 53 ] Furthermore, the TBR of the as‐bonded Si/Si interface fabricated by SAB was found to have a thermal resistance equivalent to that of micrometer‐thick bulk Si. [ 54 ] For the GaN‐on‐diamond structures developed by crystal growth and low‐temperature bonding technologies, the introduction of a transition layer or adhesion layer is essential, but this will result in a double heterogeneous interface.…”
Section: Resultsmentioning
confidence: 99%
“…21(c). Such an intermediate layer, which was a mixture of C and Cu atoms as was confirmed by EDX analysis, 110) could be the origin of thermal stability of interfaces. Using the time domain pulsed-light-heating thermoreflectance technique, 111) the thermal boundary resistance of as-bonded diamond//Cu interfaces (17 ± 2 m 2 • K/GW) was found to be close to that of interfaces prepared by evaporating Cu on-diamond (17 ± 3 m 2 • K/GW).…”
Section: Diamond//si Junctions 101)mentioning
confidence: 64%